When timing matters—misdesigned dam filling impacts hydropower sustainability - Zaniolo, Marta; Giuliani, Matteo; Sinclair, Scott; Burlando, Paolo; Castelletti, Andrea (Nature communications, 2021)
Decades of sustainable dam planning efforts have focused on containing dam impacts in regime conditions, when the dam is fully filled and operational, overlooking potential disputes raised by the filling phase. Here, we argue that filling timing and operations can catalyze most of the conflicts associated with a dam’s lifetime, which can be mitigated by adaptive solutions that respond to medium-to-long term hydroclimatic fluctuations. Our retrospective analysis of the contested recent filling of Gibe III in the Omo-Turkana basin provides quantitative evidence of the benefits generated by adaptive filling strategies, attaining levels of hydropower production comparable with the historical ones while curtailing the negative impacts to downstream users. Our results can inform a more sustainable filling of the new megadam currently under construction downstream of Gibe III, and are generalizable to the almost 500 planned dams worldwide in regions influenced by climate feedbacks, thus representing a significant scope to reduce the societal and environmental impacts of a large number of new hydropower reservoirs. Filling of dams, when coinciding with droughts, can lead to severe downstream hydrology and ecology problems. The authors hence here provide a multisectoral perspective, using a dam in Ethiopia as an example, to develop adaptive filling solutions that support decision making, favourable filling timing and an effective filling policy.